El Género Y El Consumo Hedonista En Saltillo, Coahuila - Ruiz, Edith Reyes; Wong, Adriana Méndez; Siller, Jesús Francisco Mellado; de la Vega, Laura Estela Fischer (European Scientific Journal, ESJ, 2017)
In the marketing context, it is essential to know the market. That is why there is a necessity to investigate its behavior in regards to clothes purchase. The aim of this study is to develop a model from the conceptual perspective of the shopper typology scale (Chengedzai, Manillall & Lawrence, 2014) in its factor: Hedonist consumer. The study included 250 adult participants (59.2% women and 40.8% men) living in the City of Saltillo, Coahuila, Mexico. A discriminate analysis was performed to get a membership model of the gender of the variables of Hedonist trend consumer. The results of the findings show meaningful differences between men and women. Women enjoy more shopping, and they have fun while doing it. They also spend more time in this activity.